Nonviral Delivery Systems of mRNA Vaccines for Cancer Gene Therapy - Yusi Wang; Rui Zhang; Lin Tang; Li Yang (MDPI AG, 2022)
In recent years, the use of messenger RNA (mRNA) in the fields of gene therapy, immunotherapy, and stem cell biomedicine has received extensive attention. With the development of scientific technology, mRNA applications for tumor treatment have matured. Since the SARS-CoV-2 infection outbreak in 2019, the development of engineered mRNA and mRNA vaccines has accelerated rapidly. mRNA is easy to produce, scalable, modifiable, and not integrated into the host genome, showing tremendous potential for cancer gene therapy and immunotherapy when used in combination with traditional strategies. The core mechanism of mRNA therapy is vehicle-based delivery of in vitro transcribed mRNA (IVT mRNA), which is large, negatively charged, and easily degradable, into the cytoplasm and subsequent expression of the corresponding proteins. However, effectively delivering mRNA into cells and successfully activating the immune response are the keys to the clinical transformation of mRNA therapy. In this review, we focus on nonviral nanodelivery systems of mRNA vaccines used for cancer gene therapy and immunotherapy.